Midazolam no estresse por contenção em aves silvestres - Vila, Laura García (2015)
Restraint induced stress in wild birds can be life threatening. Research for alternatives that minimize those risks iswell justified, sedation beinga suitable option. In the present study midazolam sedation was tested in two species of wild birds. Twenty-one blue-and-yellow macaws were randomly assigned in two groups, one receiving saline solution (control group) and the other approximately 7.5 mg/kg of midazolam (midazolam group) via an intranasal spray, in two different moments with a washout period of two months. Fourteen greater rheas were submitted to a similar protocol; however, the midazolam dosage was 1 mg/kg via an intramuscular route. After 10 min following sedative/saline application, physical exam (heart rate, respiratory rate and temperature) and venous blood collectionwere performed. Blood samples were processed for hemogasometry (only with macaws), hematology and biochemistry analyses. In macaws, midazolam application produced sedation; lower values for physical exam parameters and significantly (p<0.05) lower lactate, base excess and chloride concentrations, while pCO2, ctCO2 and HCO3 values were higher when compared with control group. In rheas, the only significant difference was the respiratory rate, being higher in the midazolam group. In macaws midazolam attenuated metabolic acidosis derived from restraint, showing a positive effect on stress reduction, proving an effective and safe alternative. In response to midazolam rheas showed inconstant reaction depending among individuals, with no reliable effect on stress restraint reduction.